Sponsored links: Algebra eBooks
 

Related

programmode-solve-true

programmode: true;

solve([0.226*x-195/x=...

Calculate

programmode

? programmode;

Calculate

programmode-solve-true

programmode: true;

solve([0.226*x-195/x=...

Calculate

programmode

? programmode;

Calculate

programmode

Run Example
(%i1)e1: x1*(sqrt(-d^2-c^2-b^2)) + x2*b + x3*c + x4*d = 0;
                                            2    2    2
(%o1)          d x4 + c x3 + b x2 + sqrt(- d  - c  - b ) x1 = 0
(%i2) e2: x1*(-b) + x2*sqrt(-d^2-c^2-b^2) + x3*(-d) + x4*c = 1;
                                     2    2    2
(%o2)          c x4 - d x3 + sqrt(- d  - c  - b ) x2 - b x1 = 1
(%i3) e3: x1*(-c) + x2*d + x3*sqrt(-d^2-c^2-b^2) + x4*(-b) = (-c*sqrt(-d^2-c^2-b^2) - bd)/(d^2 + c^2);
                       2    2    2
(%o3) - b x4 + sqrt(- d  - c  - b ) x3 + d x2 - c x1 = 
                                                              2    2    2
                                                  - c sqrt(- d  - c  - b ) - bd
                                                  -----------------------------
                                                              2    2
                                                             d  + c
(%i4) e4: x1*(-d) + x2*(-c) + x3*b + x4*sqrt(-d^2-c^2-b^2) = (-d*sqrt(-d^2-c^2-b^2) + bc)/(d^2 + c^2);
              2    2    2
(%o4) sqrt(- d  - c  - b ) x4 + b x3 - c x2 - d x1 = 
                                                                   2    2    2
                                                    bc - d sqrt(- d  - c  - b )
                                                    ---------------------------
                                                               2    2
                                                              d  + c
(%i5)  [globalsolve: true, programmode: true, solvradcan: true, llinsolce_param: true ];
(%o5)                      [true, true, true, true]
(%i6) linsolv([e1, e2, e3, e4], [x1, x2, x3, x4]);
                                            2    2    2
(%o6) linsolv([d x4 + c x3 + b x2 + sqrt(- d  - c  - b ) x1 = 0, 
                      2    2    2
c x4 - d x3 + sqrt(- d  - c  - b ) x2 - b x1 = 1, 
                 2    2    2
- b x4 + sqrt(- d  - c  - b ) x3 + d x2 - c x1 = 
            2    2    2
- c sqrt(- d  - c  - b ) - bd          2    2    2
-----------------------------, sqrt(- d  - c  - b ) x4 + b x3 - c x2 - d x1 = 
            2    2
           d  + c
               2    2    2
bc - d sqrt(- d  - c  - b )
---------------------------], [x1, x2, x3, x4])
           2    2
          d  + c
(%i7) 
Run Example
display2d:false;

(%o1) false
(%i2) 
programmode:false;

(%o2) false
(%i3) 
f: a*x*x+b*x+c;

(%o3) a*x^2+b*x+c
(%i4) 
solve(f,x);
solve: solution:

(%t4) x = -(sqrt(b^2-4*a*c)+b)/(2*a)

(%t5) x = (sqrt(b^2-4*a*c)-b)/(2*a)
(%o5) [%t4,%t5]
(%i6) 
Run Example
e1 : a*ky*(Kz1*ep+Kz2*em)-kh*(Ky1*ep-Ky2*em)=bxu;
(%o1)         a ky (em Kz2 + ep Kz1) - kh (ep Ky1 - em Ky2) = bxu
(%i2) e2: kh*(Kx1*ep-Kx2*em)-a*kx*(Kz1*ep+Kz2*em) =byu;
(%o2)         kh (ep Kx1 - em Kx2) - a kx (em Kz2 + ep Kz1) = byu
(%i3) e3: a*kx*(Ky1*ep+Ky2*em)-a*ky*(Kx1*ep+Kx2*em) = bzu;
(%o3)        a kx (em Ky2 + ep Ky1) - a ky (em Kx2 + ep Kx1) = bzu
(%i4) e4 : a*ky*(Kz1*em+Kz2*ep)-kh*(Ky1*em-Ky2*ep)=bxl;
(%o4)         a ky (ep Kz2 + em Kz1) - kh (em Ky1 - ep Ky2) = bxl
(%i5) e5: kh*(Kx1*em-Kx2*ep)-a*kx*(Kz1*em+Kz2*ep) =byl;
(%o5)         kh (em Kx1 - ep Kx2) - a kx (ep Kz2 + em Kz1) = byl
(%i6) e6: a*kx*(Ky1*em+Ky2*ep)-a*ky*(Kx1*em+Kx2*ep) = bzl;
(%o6)        a kx (ep Ky2 + em Ky1) - a ky (ep Kx2 + em Kx1) = bzl
(%i7)  [globalsolve: false, programmode: true];
(%o7)                            [false, true]
(%i8) linsolve([e1,e2,e3,e4,e5,e6],[Kx1,Kx2,Ky1,Ky2,Kz1,Kz2]);
(%o8)                                 []
(%i9) 

Related Help

Help for Programmode